Wpływ dezintegracji termicznej na szybkość biodegradacji odpadów organicznych = Influence of thermal disintegration on rate of organic waste biodegradation - Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Disintegration is the physical-chemical liquefaction of complex organic substrates to molecular products in the form of sugars, proteins and fats and persistent fractions. In the literature, this phase of degradation is commonly called hydrolysis. This paper presents the results of determining of the rate constant for the biodegradation of raw biofraction of municipal waste and thermally disintegrated fraction.
Keywords: hydroliza; odpady komunalne; dezintegracja termiczna; hydrolysis; municipal waste; thermal disintegration